2017
DOI: 10.1177/1049909117723618
|View full text |Cite
|
Sign up to set email alerts
|

Primary Palliative Care Education: A Pilot Survey

Abstract: The demand for palliative services is outpacing the availability of specialist palliative care clinicians. One strategy to fill this gap is to improve "primary palliative care" skills and knowledge of all clinicians who care for seriously ill patients. Previous educational efforts have shown mixed results, and one possible explanation is unrecognized discordance of educational goals between those offering education and potential primary palliative care learners. The article describes the results and feasibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 26 publications
0
17
0
4
Order By: Relevance
“…On the other hand, PC specialists have limited time for each patient and also mandatory time-consuming documentation requirements. At the same time education is needed, which was addressed by requesting physicians and PC specialists, however literature indicates that non-PC-specialists are not as much in favor of receiving education than PC specialists in providing it [50].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, PC specialists have limited time for each patient and also mandatory time-consuming documentation requirements. At the same time education is needed, which was addressed by requesting physicians and PC specialists, however literature indicates that non-PC-specialists are not as much in favor of receiving education than PC specialists in providing it [50].…”
Section: Discussionmentioning
confidence: 99%
“…23 Our findings also are consistent with similar research identifying interactive workshops as the preferred modality for palliative care training among primary care physicians, hospitalists, geriatricians, and neurologists. 7 An educational and training dynamic based on social-interactive connections among learners is considered optimal for sustaining participant interest in the learning process, and building social-interactive engagement into Web-based education has been shown to help reduce the dropout rate among Web-based learners. 24 Our research revealed that PCCT members prefer in-person palliative care education and training because of its flexibility in addressing trainees' unique needs and specific issues.…”
Section: Discussionmentioning
confidence: 99%
“…6 This is attributed, in part, to a growing demand for services as well as shortages in the palliative care workforce and the need to train additional providers to support the care of people living with serious and life-limiting illness and imminently dying inpatients. 7,8 Palliative care educational and training initiatives can be instrumental in expanding the palliative care workforce, 9 enhancing the skills of current providers, 10 increasing the frequency of use and scope of palliative care consult teams, 11 and facilitating the integration of palliative care modalities into the acute care setting. 12 There is growing interest in how palliative care education and training is delivered, with an emerging body of research examining education and training preferences for computerbased versus in-person approaches.…”
mentioning
confidence: 99%
“…The results obtained highlighted the significant amount of knowledge acquired by the participants after training, in terms of increasing their knowledge of PC and in terms of the change in meaning that they attributed to phenomena related to chronicity and incurability, which they encounter daily in their professional practice [42]. Turrillas et al [25], through a systematic review of the existing literature on the subject, showed that in the analysed studies, despite the use of various original or modified educational training and assessment methods of which psychometric characteristics were often not reported, all educational methods have allowed non-palliative care professionals to improve their knowledge and preparation regarding palliative care and EoL patient management.…”
Section: Discussionmentioning
confidence: 99%